Free zones of the Republic of Serbia - business results 2011-2021 and future development - Simonovic, Aleksandar; Kostic, Dragan (Serbian Journal of Management, 2022)
Free zones are an effective economic instrument that provide the host country with a rapid influx of investments, increased employment, access to new technologies, education, work, industrialization and increased exports. Serbian free zones specialize in industrial production intended for export. They provide their tenants (companies who use the zones) with ease in doing business by exempting them from customs and tax duties. Within certain free zones in Serbia, there are benefits offered by local self-government and they can contribute to a more favorable investment environment compared to other locations.About 10,000 free zones in the world participate in the daily battle for investors, including 82 free zones in the European Union. By offering various services, free zones fight to retain existing and attract new investors, and the platform of free zones provides the fastest and most practical way of flexible development in international trade and increasing the attractiveness of countries for productive international investments.A detailed analysis of the results of the establishment and operation of free zones in Serbia has never been done until now. Previous analyzes were limited to textual and tabular presentations of the results of free zone operations in the previous year and did not provide any relevant conclusions and did not propose measures to improve the operation of both free zones and free zone user companies, nor the applied concept of free zones in Serbia.
Keywords: Free zones; Special Economic zones; Invest in Serbia